The Influence of Compensation and Benefits on Employee Performance at Aston Batam Hotel and Residence - Yogi dirvana putra Yogi; Pasaribu (Journal of Multidimensional Management, 2025)
This study investigates the influence of compensation and benefits on employee performance in the hospitality industry, with a case study at Aston Batam Hotel and Residence, Indonesia. A quantitative approach with a causal-associative design was employed, involving 82 employees selected using convenience sampling. Data were collected through a structured questionnaire measured on a five-point Likert scale and analyzed using multiple linear regression with SPSS 26.0, including validity, reliability, and classical assumption tests. The results reveal that compensation and benefits, both individually and simultaneously, do not have a significant effect on employee performance, with a coefficient of determination (R²) of only 0.030. This finding suggests that compensation and benefits explain merely 3% of performance variance, while 97% is influenced by other factors such as motivation, leadership, organizational culture, and workplace environment. The study highlights the need for hotel management to adopt a more comprehensive human resource strategy that integrates financial and non-financial rewards with leadership development and organizational support to enhance employee performance and sustain competitiveness in the hospitality industry.